The Effect of Lighting Intensity on Visual Comfort in The Sacred Space Of Buddhist Temple - Vivianie Fortuna; Widyarko Widyarko; Joice Sandra Sari (Journal of Architectural Design and Urbanism, 2022)
A Buddhist temple is a sacred Buddhist space where the building users require certain visual comfort conditions. The issue is that the temple's architectural style varies according to the local context and the type of belief it teaches. Implementing certain architectural styles will affect the interior space's artificial lighting design, which eventually affects the visual comfort of building users. Therefore, this study aims to determine the effect of artificial lighting on the building user's visual comfort in two different temple case studies that use dissimilar architectural styles in Medan City, Indonesia. Two data collection methods were used in this study. The first was by measuring the room's illumination level using a handheld lux meter. Secondly, through a survey/ questionnaire to find out user's perception of visual comfort related to the usage of artificial lighting during two activities in the sacred space in the temple: praying and reciting the Sutras. As a result, the two temples were identified using almost the same principle of applying artificial lighting, which aligns with Buddhism's purpose of enlightenment, 'the journey from dark to light.' The data collection results also show similar results. Both have illumination levels below the number stated in the visual comfort standards. While on the contrary, the majority of survey respondents from both cases felt visually comfortable during their activities in the case study. This study proves that the lighting design capable of providing positive visual impacts for users can rely on the technique and method of applying lighting distribution.